Педагогикалық ЖОО-ның болашақ мамандарының ақпараттық құзыреттілігін қалыптастыру жəне дамыту - Айтбенова, А.А. (My University, 2016)
The article describes the foundation and development of the future specialists with information competence pedagogical Institute. The distinction, tasks and function, the main components of model of creation of future specialist with information competence is also shown.
Keywords: information; competence; information competence; future specialist; components.